Method for synthesizing phosphoric acid ferric pyrophosphate and preparing phosphoric acid ferric pyrophosphate sodium positive electrode material
Synthesizing sodium ferric pyrophosphate positive electrode material through the precursor method, solving the problems of low electronic conductivity and heterogeneous phase generation of NFPP materials, achieving high purity and excellent electrochemical performance positive electrode material, and improving the energy density of sodium ion batteries and cycle stability.
Patent Information
- Application Number
- CN202411517972.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The existing sodium ion battery positive electrode material, sodium ferric pyrophosphate (NFPP), has a low inherent electron conductivity, resulting in slow electrode reaction kinetics and difficult to synthesize high-purity phase materials. There are often heterogeneous phases without electrochemical activity, which hinders Na+ Diffusion and reduce reversible capacity.
The precursor method is used to synthesize the positive electrode material of Na4Fe3(PO4)2(P2O7) and the precursor Fe6(PO4)2(P2O7)3 with the Fe and P elements arranged in a long range and evenly arranged on the atomic scale. The co-precipitation reaction and subsequent sintering process inhibit the formation of NaFePO4 heterophase, and improve the morphology and electrochemical properties of the material through spray drying and carbon coating technology.
The high purity and excellent electrochemical properties of Na4Fe3(PO4)2(P2O7) cathode material are achieved, including high compaction density, good spherical shape and electrochemical activity, which significantly improves the energy density and cycle stability of the material.
Smart Images

Figure CN119390031A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion battery positive electrode materials, and in particular relates to a method for synthesizing ferric phosphate pyrophosphate and preparing sodium ferric phosphate pyrophosphate positive electrode materials. Background Art
[0002] In the development and utilization of renewable clean energy, electrochemical energy storage technology based on rechargeable batteries (especially lithium-ion batteries) plays a key "foundation" role. However, limited lithium resources can hardly meet the growing demand for energy storage. Sodium-ion batteries have become an ideal substitute for lithium-ion batteries due to the abundant sodium reserves in the earth's crust and their similar electrochemical behavior to lithium-ion batteries, showing great application potential in electrochemical energy storage systems.
[0003] As an important component of sodium-ion batteries, cathode materials largely determine the energy density and cost of batteries. The development of cathode materials with high capacity, high voltage and long cycle stability is a research hotspot and frontier issue for sodium-ion batteries today. So far, Prussian blue compounds, layered oxides and polyanionic compounds have become the three main technical routes for sodium cathodes. Although Prussian blue compounds and layered oxides have high specific capacities, their respective shortcomings (such as the difficulty in removing the crystal water of Prussian blue compounds and the poor air stability of layered oxides) limit their practical applications.
[0004] In contrast, polyanionic compounds have a stable structural framework and higher operating voltage, and exhibit excellent air stability, thermal stability and cycle stability, and are considered to be the best choice for sodium-ion battery cathode materials. Among the many polyanionic cathode materials (such as phosphates, pyrophosphates, fluorophosphates, sulfates and silicates), the sodium superionic conductor type iron-based mixed phosphate Na4Fe3(PO4)2(P2O7) material (sodium iron phosphate pyrophosphate, hereinafter referred to as NFPP) is composed of high-abundance, low-cost and non-toxic elements such as Fe and P, and has high structural stability (volume strain during sodiumation / de-sodiumation process <4%), moderate theoretical capacity (128.9mAh g-1) and operating voltage (3.0V vs.Na+ / Na), and is receiving widespread attention. However, there are still some problems to be overcome in the practical application of NFPP. First, similar to other polyanionic cathode materials, NFPP has a low intrinsic electronic conductivity, which leads to slow kinetics of electrode reactions and a greater impact on electrochemical performance. Secondly, it is difficult to synthesize high-purity NFPP. During the synthesis process, an electrochemically inactive sodium iron phosphate ore-type NaFePO4 (NFP) impurity phase often appears, which hinders the Na + diffusion and reduce the reversible capacity of the material.
[0005] At present, the synthesis process of NFPP is mostly spray drying-solid phase sintering method or ball milling assisted solid phase sintering method. The raw materials use separate phosphates, sodium salts and iron salts. There is no feasible precursor synthesis process, and it is difficult to achieve uniform mixing of multiple elements at the atomic scale, which leads to the formation of inactive impurities during the sintering synthesis process. In addition, the current spray drying process mostly uses nitrate as a raw material, which has a very high burn-off rate and produces tail gases such as nitrogen oxides, which easily cause the fragmentation of spherical particles. The obtained NFPP material has a low vibration and compaction density, which limits the improvement of the material's energy density. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a method for synthesizing ferric phosphate pyrophosphate and preparing sodium ferric phosphate pyrophosphate positive electrode material, and the prepared positive electrode material has better electrochemical performance.
[0007] The technical solution adopted by the present invention to solve the technical problem is a method for synthesizing ferric phosphate pyrophosphate and preparing sodium ferric phosphate pyrophosphate positive electrode material, comprising the following steps:
[0008] S1, preparing iron salt solution, preparing phosphate solution, preparing pyrophosphate solution, preparing ammonia solution, preparing acid solution;
[0009] S2, preparing a reaction base liquid, then adding an iron salt solution, a phosphate solution, and a pyrophosphate solution to the reaction base liquid, using an ammonia solution and / or an acid solution to control the pH value, and performing a coprecipitation reaction under stirring to obtain a slurry A;
[0010] S3, filtering and washing slurry A, adding water and re-slurrying to obtain slurry B;
[0011] S4, heating the slurry B to the crystallization temperature, and crystallizing it under stirring to obtain slurry C;
[0012] S5, filtering the slurry C, and drying the precipitate to obtain precipitate D;
[0013] S6. Sinter the precipitate D at a certain temperature to remove the crystal water and obtain ferric phosphate pyrophosphate Fe6(PO4)2(P2O7)3.
[0014] S7, adding the ferric phosphate pyrophosphate, sodium source, and carbon source obtained in step S6 into water for slurrying, and then sand-milling (preferably in a sand mill) to obtain slurry E;
[0015] S8, spray drying the slurry E to obtain a mixed powder F;
[0016] S9. Sinter the mixed powder F in an inert or reducing atmosphere to obtain the carbon-coated sodium ion battery positive electrode material sodium iron phosphate pyrophosphate Na4Fe3(PO4)2(P2O7) / C.
[0017] Furthermore, in step S1, the iron salt is at least one of ferric nitrate, ferric chloride, ferric sulfate, ferric dihydrogen phosphate, ferric tribromide, etc. The concentration of the iron salt solution is preferably 40 to 120 g / L in terms of Fe mass concentration.
[0018] Furthermore, in step S1, the phosphate solution is formed by dissolving at least one of ammonium dihydrogen phosphate, ammonium hydrogen phosphate, ammonium phosphate, sodium dihydrogen phosphate, sodium hydrogen phosphate, sodium phosphate, and phosphoric acid in water. The concentration of the phosphate ion is preferably 0.05 to 0.15 mol / L.
[0019] Furthermore, in step S1, the pyrophosphate solution is formed by dissolving at least one of sodium pyrophosphate and potassium pyrophosphate in water. The concentration of pyrophosphate ions is preferably 0.05 to 0.25 mol / L. The acid is preferably at least one of sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid.
[0020] Furthermore, in step S1, the phosphate solution and the pyrophosphate solution may also be prepared by dissolving solutes in water to form a solution.
[0021] Further, in step S2, the reaction base liquid is water. Ammonia or an acid solution can be selected to adjust the reaction base liquid to a specific pH value. Specifically, the pH of the base liquid is adjusted to the pH at which the coprecipitation reaction is desired to be reacted.
[0022] Furthermore, in step S2, the pH value is controlled to be 2 to 6. If the pH is too low, a large amount of pyrophosphate will be hydrolyzed into phosphate, and the target product cannot be obtained; if the pH is too high, the hydrolysis of trivalent iron will be violent, and a large amount of ferric hydroxide will be produced, and the target product cannot be obtained either.
[0023] Further, in step S2, a reaction base solution is prepared, and then the iron salt solution, the phosphate solution, and the pyrophosphate solution are introduced into the reaction base solution in parallel. The parallel introduction is convenient for controlling pH, adjusting the rate balance of nucleation and grain growth, and controlling the particle size and morphology.
[0024] Further, in step S2, the amount of iron salt solution, phosphate solution and pyrophosphate solution introduced is based on the molar ratio of each element in the ferric phosphate pyrophosphate molecular formula, and the amount introduced is according to Fe:PO4:P2O7=5.5-6.0:2-2.2:3-3.2 (preferably 5.7-6.0:2:3, more preferably 6:2:3).
[0025] Furthermore, in step S2, the reaction time of the coprecipitation reaction is greater than or equal to 0.5 hours, mainly to ensure that the precipitation reaction is complete. Too long a time is not conducive to the synthesis efficiency, and too short a time will lead to incomplete precipitation.
[0026] Further, in step S3, the slurry A is filtered and washed for more than 2 times, preferably 3-5 times.
[0027] Furthermore, in step S3, water is added to re-slurry, and the mass concentration of Fe after adding water is preferably 15-25 g / L, and the mass concentration of Fe is more preferably 18-20 g / L.
[0028] Furthermore, in step S4, the crystallization temperature is 80-95°C. The purpose of crystallization is to allow the particles to continue to grow and to eliminate the possible small amount of iron hydroxide impurities and some ionic impurities (such as Na, Mg, Ca, etc.) wrapped in the gaps between the particles. Too high a temperature has little effect, mainly considering the boiling point of water; too low a temperature cannot effectively eliminate iron hydroxide and other impurities.
[0029] Furthermore, in step S4, the crystallization time is more than 2 hours.
[0030] Furthermore, in step S6, the sintering temperature is 300-600°C, and the sintering time is 2-4 hours. If the sintering temperature is too high, the particles will be severely hardened and difficult to break; if the sintering temperature is too low, the crystal water cannot be fully eliminated; if the sintering time is too long, the particles will grow together, which is not conducive to the particle size; if the sintering time is too short, the crystal water cannot be completely removed.
[0031] Further, in step S7, the amount of ferric pyrophosphate and sodium source is determined according to the element molar ratio of Na4Fe3(PO4)2(P2O7), the amount of Fe can fluctuate between 2.85 and 3.00, the amount of Na can fluctuate between 3.95 and 4.05, and the amount of carbon source is 10% to 150% of the mass of the theoretical output of sodium ferric pyrophosphate;.
[0032] Furthermore, in step S7, the liquid-to-solid ratio of pulping is 10:1 to 30:1, preferably 20:1.
[0033] Furthermore, in step S7, the sand milling process controls the particle size of the output material to be 50-150 nm. Too large or too small particle size of the output material will affect the granulation effect of spray drying.
[0034] Further, in step S7, the sodium source is one or more of sodium carbonate, sodium bicarbonate, sodium acetate, sodium hydroxide, and sodium nitrate; the carbon source is one or more of citric acid, glucose, polyvinyl alcohol, polyethylene glycol, polydopamine, polyvinyl pyrrolidone, resorcinol-formaldehyde resin, sucrose, fructose, starch, cellulose, Ketjen black, carbon nanotubes, and graphene.
[0035] Further, in step S9, the inert or reducing atmosphere is one or more of nitrogen, argon, nitrogen-hydrogen mixed gas, and argon-hydrogen mixed gas. The volume ratio of hydrogen in the nitrogen-hydrogen mixed gas is 5-10% (preferably 5%). The volume ratio of hydrogen in the argon-hydrogen mixed gas is 5-10% (preferably 5%).
[0036] Furthermore, in step S9, the sintering temperature used is 450-600°C and the sintering time is 5-20 hours. If the sintering temperature is too high or too low, the Na4Fe3(PO4)2(P2O7) material cannot be formed, and if the sintering time is too long or too short, the particle size is mainly affected.
[0037] Furthermore, in step S9, the mixed powder F can be pre-sintered in an inert or reducing atmosphere before sintering; the pre-sintering temperature is 200-400°C, and the pre-sintering time is 4-8h. Pre-sintering is to fully melt the sodium source and the carbon source. At this time, the carbon source usually expands in volume. In order to improve the contact effect of the raw materials and the powder density, the pre-sintering is followed by tableting and secondary sintering. The advantage is good carbon coating effect and high powder density.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] The present invention synthesizes Na4Fe3(PO4)2(P2O7) cathode material by a precursor method, and pre-synthesizes a precursor phosphate iron pyrophosphate Fe6(PO4)2(P2O7)3 in which Fe and P elements are arranged in a long-range orderly and uniform manner on the atomic scale. In this structure, Fe and P elements are arranged uniformly at the atomic level, and in the subsequent sintering process, the NaFePO4 impurity phase generated by uneven ion distribution is effectively suppressed; in addition, the precursor synthesis method avoids the problem of generating a large amount of gas and a high burn-off rate when sintering with raw materials such as nitrates, acetates, and oxalates. The obtained Na4Fe3(PO4)2(P2O7) cathode material has good sphericity and high compaction density (the compaction density can reach 2.30g / cm 3 Even 2.35g / cm 3 The precursor morphology and particle size are controllable, which can effectively solve the problem of the generation of inactive impurity phase NaFePO4 in the synthesis process of sodium iron phosphate pyrophosphate, and the raw material utilization rate is high. The tap density and compaction density of the synthesized positive electrode material are large, and the electrochemical performance is excellent. Therefore, the preparation method of the present invention has a short process and a simple process, and effectively improves the product purity and the physical and chemical indicators of the material, and can greatly improve the electrochemical performance of the prepared positive electrode material compared with the prior art.
[0040] The present invention pre-synthesizes a Fe6(PO4)2(P2O7)3 precursor with long-range orderly and uniform arrangement of Fe and P elements, realizes uniform mixing at the atomic level, and the morphology and particle size of the material are precisely controllable, effectively avoiding the problem of inactive impurities caused by uneven ion distribution during the sintering process, and greatly improving the purity of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 XRD patterns of ferric phosphate pyrophosphate (i.e., precursor) and sodium ferric phosphate pyrophosphate (NFPP for short) prepared in Example 1;
[0042] Figure 2 This is a SEM image of the sodium iron pyrophosphate material prepared in Example 1;
[0043] Figure 3 This is the first cycle charge and discharge curve of the sodium iron pyrophosphate material prepared in Example 1;
[0044] Figure 4 This is a rate performance diagram of the sodium iron pyrophosphate material prepared in Example 1;
[0045] Figure 5 This is a cycle performance diagram of the sodium iron pyrophosphate material prepared in Example 1;
[0046] Figure 6 The XRD pattern of the sodium iron pyrophosphate material prepared in Comparative Example 1;
[0047] Figure 7 This is a SEM image of the sodium iron pyrophosphate material prepared in Comparative Example 1;
[0048] Figure 8 This is the first cycle charge and discharge curve of the sodium iron pyrophosphate material prepared in Comparative Example 1;
[0049] Fig. 9 This is a rate performance diagram of the sodium iron pyrophosphate material prepared in Comparative Example 1. DETAILED DESCRIPTION
[0050] The present invention will be further described below in conjunction with specific embodiments and accompanying drawings, but the present invention is not limited to the following embodiments. Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0051] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified. The percentages described in this application are by mass percentages unless otherwise specified.
[0052] Example 1
[0053] A method for synthesizing ferric phosphate pyrophosphate and preparing sodium ferric phosphate pyrophosphate positive electrode material comprises the following steps:
[0054] (1) Add 17.5 mmol of Fe(NO3)3·9H2O to 20 mL of deionized water and stir to dissolve to obtain solution A; add 6 mmol of NH4H2PO4 and 9 mmol of Na4P2O7 to 30 mL of deionized water and stir to dissolve to obtain solution B; 25% concentrated ammonia water is used as solution C; dilute concentrated sulfuric acid to 4 mol·L -1 , and obtain solution D;
[0055] (2) Add 20 mL of deionized water to the reactor, start stirring, and adjust the pH to 4.0 with an acid solution; flow solutions A to D into the reactor in parallel, maintain the reaction pH at 4.0 by controlling the flow rate, and stir the reaction at 50° C. and 300 rpm for 2.5 h to obtain slurry A;
[0056] (3) After slurry A was filtered and washed twice, 200 mL of deionized water was added to re-slurry to obtain slurry B;
[0057] (4) raising the temperature of slurry B to 90° C., stirring at a rotation speed of 100 rpm, and crystallizing for 2 h to obtain slurry C;
[0058] (5) Filtering, washing and drying the slurry C to obtain a white powder D;
[0059] (6) calcining the white powder D at 500 °C for 2 h to obtain a precursor powder;
[0060] (7) Take 2 g of the precursor powder, add 0.6382 g of sodium carbonate and 0.3 g of anhydrous glucose into 100 mL of deionized water, stir and slurry, and then sand grind. During the sand grinding process, the particle size of the output is controlled to be 50 to 150 nm; obtain slurry E;
[0061] (8) The sand-milled slurry E was spray-dried at a spray temperature of 200 °C and a flow rate of 200 mL min -1 , to obtain mixed powder F;
[0062] (9) The mixed powder F was pre-sintered at 300° C. for 5 h in an argon-hydrogen atmosphere with a volume percentage of argon 95% / hydrogen 5%, the sintered product was pressed into sheets, and then sintered at 550° C. for 10 h to obtain a carbon-coated sodium ion battery positive electrode material, sodium iron phosphate pyrophosphate Na4Fe3(PO4)2(P2O7) / C.
[0063] The XRD spectrum of the positive electrode material prepared in this example is as follows Figure 1 As shown, from Figure 1 It can be seen that the synthesized sodium iron phosphate pyrophosphate has an orthorhombic crystal structure with a space group of Pn21a. At the same time, the Rietveld structure refinement of the XRD pattern shows high phase purity and no impurity phase. Figure 2 As shown, from Figure 2 It can be seen that the material particles have good sphericity and the surface is covered with a uniform carbon layer.
[0064] The obtained positive electrode material was mixed with a conductive agent and PVDF, slurried and coated on aluminum foil. A sodium sheet was used as the negative electrode and a 1MNaClO4 EC:PC (1:1Vol%, containing 5% FEC) solution was used as the electrolyte to assemble a CR2032 button half-cell to test the electrochemical properties of the positive electrode material.
[0065] The first cycle charge and discharge curve of the assembled battery is as follows: Figure 3 As shown in the figure, the rate performance diagram is as follows Figure 4 As shown, the cycle performance diagram is as follows Figure 5 The compaction density of the obtained Na4Fe3(PO4)2(P2O7) cathode material is 2.35g / cm 3 The positive electrode material obtained in this embodiment has a 0.1C first discharge capacity greater than 120 mAh / g, a 10C high rate capacity greater than 100 mAh / g, and a capacity retention rate greater than 99% after 200 cycles at 1C.
[0066] Comparative Example 1
[0067] The sodium iron phosphate pyrophosphate positive electrode material is prepared by a nitrate solution spray drying method, comprising the following steps:
[0068] (1) Dissolve 15 mmol of Fe(NO3)3·9H2O, 20 mmol of NaH2PO4·H2O, and 20 mmol of citric acid monohydrate in 150 mL of deionized water to obtain solution A;
[0069] (2) Solution A was spray dried at a spray temperature of 200 °C and a flow rate of 200 mL min -1 , to obtain mixed powder B;
[0070] (3) The mixed powder B is placed in a 95% / 5% argon-hydrogen atmosphere, pre-sintered at 300°C for 5 hours, the sintered product is pressed into sheets, and then sintered at 550°C for 10 hours to obtain a carbon-coated sodium ion battery positive electrode material, sodium iron phosphate pyrophosphate Na4Fe3(PO4)2(P2O7) / C.
[0071] The XRD spectrum of the positive electrode material prepared in this comparative example is as follows Figure 6 As shown, SEM images are Figure 7As shown. Figure 1 and Figure 2 It can be seen that the NFPP positive electrode material prepared in Comparative Example 1 has obvious impurities compared to that in Example 1, and the material particles have obvious fragmentation.
[0072] The same method as in Example 1 was used to assemble a CR2032 button-type half-cell and test the electrochemical performance of the positive electrode material. The first cycle charge and discharge curve of the assembled battery is shown in Figure 8 As shown in the figure, the rate performance diagram is as follows Fig. 9 The 0.1C first discharge specific capacity of the material is 91.4 mAh / g, and the 10C capacity is 76.9 mAh / g, both of which are much lower than those in Example 1.
[0073] Example 2
[0074] A method for synthesizing ferric phosphate pyrophosphate and preparing sodium ferric phosphate pyrophosphate positive electrode material comprises the following steps:
[0075] (1) Add 18.0 mmol of Fe(NO3)3·9H2O to 20 mL of deionized water and stir to dissolve to obtain solution A; add 6 mmol of NH4H2PO4 and 9 mmol of Na4P2O7 to 30 mL of deionized water and stir to dissolve to obtain solution B; 25% concentrated ammonia water is used as solution C; dilute concentrated sulfuric acid to 4 mol·L -1 , and obtain solution D;
[0076] (2) Add 20 mL of deionized water to the reactor, start stirring, and use acid to adjust the pH to 6.0; flow solutions A to D into the reactor in parallel, maintain the reaction pH at 6.0 by controlling the flow rate, and stir the reaction at 50° C. and 300 rpm for 2.0 h to obtain slurry A;
[0077] (3) After slurry A was filtered and washed twice, 200 mL of deionized water was added to re-slurry to obtain slurry B;
[0078] (4) raising the temperature of slurry B to 90° C., stirring at a rotation speed of 100 rpm, and crystallizing for 2 h to obtain slurry C;
[0079] (5) Filtering, washing and drying the slurry C to obtain a white powder D;
[0080] (6) calcining the white powder D at 450 °C for 3 h to obtain the precursor powder iron phosphate pyrophosphate Fe6(PO4)2(P2O7)3;
[0081] (7) Take 2 g of the precursor powder, add 0.6382 g of sodium carbonate, 0.2 g of anhydrous glucose, and 0.1 g of polyethylene glycol to 100 mL of deionized water, stir and slurry, and then sand grind. During the sand grinding process, the particle size of the output is controlled to be 50 to 150 nm; obtain slurry E;
[0082] (8) The slurry E was spray dried at a spray temperature of 220 °C and a flow rate of 400 mL min -1 , to obtain mixed powder F;
[0083] (9) The mixed powder F is pre-sintered at 300° C. for 5 h in a high-purity argon (volume purity greater than or equal to 99.99%) atmosphere, the sintered product is pressed into sheets, and then sintered at 525° C. for 12 h to obtain a carbon-coated sodium ion battery positive electrode material, sodium iron phosphate pyrophosphate Na4Fe3(PO4)2(P2O7) / C.
[0084] The compacted density of the Na4Fe3(PO4)2(P2O7) cathode material obtained in this example is 2.36 g / cm 3 .
[0085] The electrochemical performance of the positive electrode material obtained in this example was tested using the same method as in Example 1, and the results are shown in Table 1.
[0086] Example 3
[0087] A method for synthesizing ferric phosphate pyrophosphate and preparing sodium ferric phosphate pyrophosphate positive electrode material comprises the following steps:
[0088] (1) Add 17.0 mmol of Fe(NO3)3·9H2O to 20 mL of deionized water and stir to dissolve to obtain solution A; add 6 mmol of NH4H2PO4 and 9 mmol of Na4P2O7 to 30 mL of deionized water and stir to dissolve to obtain solution B; 25% concentrated ammonia water is used as solution C; dilute concentrated sulfuric acid to 4 mol·L -1 , and obtain solution D;
[0089] (2) Add 20 mL of deionized water to the reactor, start stirring, and use acid to adjust the pH to 3.0; flow solutions A to D into the reactor in parallel, maintain the reaction pH at 3.0 by controlling the flow rate, and stir the reaction at 50° C. and 300 rpm for 2.5 h to obtain slurry A;
[0090] (3) After slurry A was filtered and washed twice, 200 mL of deionized water was added to re-slurry to obtain slurry B;
[0091] (4) raising the temperature of slurry B to 90° C., stirring at a rotation speed of 100 rpm, and crystallizing for 2 h to obtain slurry C;
[0092] (5) The slurry C is then filtered, washed, and dried to obtain a white powder D;
[0093] (6) calcining the white powder D at 480 °C for 2 h to obtain the precursor powder iron phosphate pyrophosphate Fe6(PO4)2(P2O7)3;
[0094] (7) Take 2 g of the precursor powder, add 0.6382 g of sodium carbonate, 0.2 g of anhydrous glucose, and 0.1 g of Ketjen black into 100 mL of deionized water, stir and slurry, and then sand grind. During the sand grinding process, the particle size of the output material is controlled to be 50 to 150 nm; obtain slurry E;
[0095] (8) The slurry E was spray dried at a spray temperature of 180 °C and a flow rate of 300 mL min -1 , to obtain mixed powder F;
[0096] (9) The mixed powder F was pre-sintered at 300° C. for 5 h in an argon-hydrogen atmosphere with a volume percentage of argon 95% / hydrogen 5%, the sintered product was pressed into tablets, and then sintered at 500° C. for 10 h to obtain a carbon-coated sodium ion battery positive electrode material, sodium iron phosphate pyrophosphate Na4Fe3(PO4)2(P2O7) / C.
[0097] The compacted density of the Na4Fe3(PO4)2(P2O7) cathode material obtained in this example is 2.36 g / cm 3 .
[0098] The electrochemical performance of the positive electrode material obtained in this example was tested using the same method as in Example 1, and the results are shown in Table 1.
[0099] Table 1
[0100] 0.1C discharge specific capacity 10C discharge specific capacity 1C cycle 200 times retention rate Example 1 123.5 103.3 99.3% Comparative Example 1 91.4 76.9 94.5% Example 2 118.6 92.3 98.4% Example 3 115.5 88.7 98.8%
[0101] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for synthesizing ferric phosphate pyrophosphate, characterized in that: The following steps are involved: S1, preparing iron salt solution, preparing phosphate solution, preparing pyrophosphate solution, preparing ammonia solution, preparing acid solution; S2, preparing a reaction base liquid, then adding an iron salt solution, a phosphate solution, and a pyrophosphate solution to the reaction base liquid, using an ammonia solution and / or an acid solution to control the pH value, and performing a coprecipitation reaction under stirring to obtain a slurry A; S3, filtering and washing slurry A, adding water and re-slurrying to obtain slurry B; S4, heating the slurry B to the crystallization temperature, and crystallizing it under stirring to obtain slurry C; S5, filtering the slurry C, and drying the precipitate to obtain precipitate D; S6. Sinter the precipitate D at a certain temperature to remove the crystal water and obtain ferric phosphate pyrophosphate Fe6(PO4)2(P2O7)3.
2. A method for synthesizing ferric phosphate pyrophosphate and preparing sodium ferric phosphate pyrophosphate positive electrode material, characterized in that: The following steps are involved: S1, preparing iron salt solution, preparing phosphate solution, preparing pyrophosphate solution, preparing ammonia solution, preparing acid solution; S2, preparing a reaction base liquid, then adding an iron salt solution, a phosphate solution, and a pyrophosphate solution to the reaction base liquid, using an ammonia solution and / or an acid solution to control the pH value, and performing a coprecipitation reaction under stirring to obtain a slurry A; S3, filtering and washing slurry A, adding water and re-slurrying to obtain slurry B; S4, heating the slurry B to the crystallization temperature, and crystallizing it under stirring to obtain slurry C; S5, filtering the slurry C, and drying the precipitate to obtain precipitate D; S6, sintering the precipitate D at a certain temperature to remove the crystal water, and obtaining iron phosphate pyrophosphate Fe6(PO4)2(P2O7)3; S7, adding the ferric phosphate pyrophosphate, sodium source and carbon source obtained in step S6 into water for slurrying, and then sand-milling to obtain slurry E; S8, spray drying the slurry E to obtain a mixed powder F; S9. Sinter the mixed powder F in an inert or reducing atmosphere to obtain the carbon-coated sodium ion battery positive electrode material sodium iron phosphate pyrophosphate Na4Fe3(PO4)2(P2O7) / C.
3. The method for synthesizing ferric phosphate pyrophosphate and preparing sodium ferric phosphate pyrophosphate positive electrode material according to claim 2, characterized in that: In step S1, the iron salt is at least one of ferric nitrate, ferric chloride, ferric sulfate, ferric dihydrogen phosphate, and ferric tribromide; and / or the phosphate solution is formed by dissolving at least one of ammonium dihydrogen phosphate, ammonium hydrogen phosphate, ammonium phosphate, sodium dihydrogen phosphate, sodium hydrogen phosphate, sodium phosphate, and phosphoric acid in water; and / or the pyrophosphate solution is formed by dissolving at least one of sodium pyrophosphate and potassium pyrophosphate in water.
4. The method for synthesizing ferric phosphate pyrophosphate and preparing sodium ferric phosphate pyrophosphate positive electrode material according to claim 2 or 3, characterized in that: In step S2, the pH value is 2-6; and / or the reaction time of the coprecipitation reaction is greater than or equal to 0.5 hours.
5. The method for synthesizing ferric phosphate pyrophosphate and preparing sodium ferric phosphate pyrophosphate positive electrode material according to claim 2 or 3, characterized in that: In step S2, a reaction base liquid is prepared, and then an iron salt solution, a phosphate solution, and a pyrophosphate solution are passed into the reaction base liquid in parallel; and / or, in step S2, the amount of the iron salt solution, the phosphate solution, and the pyrophosphate solution introduced is based on the molar ratio of each element in the ferric phosphate pyrophosphate molecular formula, and the amount introduced is according to Fe:PO4:P2O7=5.5-6.0:2-2.2:3-3.
2.
6. The method for synthesizing ferric phosphate pyrophosphate and preparing sodium ferric phosphate pyrophosphate positive electrode material according to claim 2 or 3, characterized in that: In step S4, the crystallization temperature is 80-95° C.; and / or the crystallization time is more than 2 hours.
7. The method for synthesizing ferric phosphate pyrophosphate and preparing sodium ferric phosphate pyrophosphate positive electrode material according to claim 2 or 3, characterized in that: In step S6, the sintering temperature is 300-600° C. and the sintering time is 2-4 h.
8. The method for synthesizing ferric phosphate pyrophosphate and preparing sodium ferric phosphate pyrophosphate positive electrode material according to claim 2 or 3, characterized in that: In step S7, the amount of ferric pyrophosphate and the sodium source is determined according to the element molar ratio of Na4Fe3(PO4)2(P2O7), the amount of Fe fluctuates between 2.85 and 3.00, the amount of Na fluctuates between 3.95 and 4.05, and the amount of carbon source is 10% to 150% of the mass of the theoretical output of sodium ferric pyrophosphate; and / or, in step S7, the sand milling process controls the discharge particle size to be 50 to 150 nm.
9. The method for synthesizing ferric phosphate pyrophosphate and preparing sodium ferric phosphate pyrophosphate positive electrode material according to claim 2 or 3, characterized in that: In step S7, the sodium source is one or more of sodium carbonate, sodium bicarbonate, sodium acetate, sodium hydroxide, and sodium nitrate; and / or the carbon source is one or more of citric acid, glucose, polyvinyl alcohol, polyethylene glycol, polydopamine, polyvinyl pyrrolidone, resorcinol-formaldehyde resin, sucrose, fructose, starch, cellulose, Ketjen black, carbon nanotubes, and graphene.
10. The method for synthesizing ferric phosphate pyrophosphate and preparing sodium ferric phosphate pyrophosphate positive electrode material according to claim 2 or 3, characterized in that: In step S9, the inert or reducing atmosphere is one or more of nitrogen, argon, nitrogen-hydrogen mixture, and argon-hydrogen mixture; and / or, in step S9, the sintering temperature used for sintering is 450-600°C, and the sintering time is 5-20 h; and / or in step S9, the mixed powder F is pre-sintered in an inert or reducing atmosphere before sintering.
Citation Information
Patent Citations
High-conductivity mixed sodium ferric pyrophosphate positive electrode material and preparation method thereof
CN117954599A
Method for synthesizing ferric sodium pyrophosphate positive electrode material by using ferric phosphate
CN118062820A
Sodium ferric phosphate pyrophosphate positive electrode material, preparation method and application
CN118472206A
Preparation method of ferrous phosphate octahydrate
CN118702079A
Cited By
Sodium-ion battery positive electrode material and preparation method thereof
CN120356931A
Preparation method of ferric sodium pyrophosphate material
CN120793873A
Pyrophosphate ferric sodium phosphate and preparation method thereof
CN121225562A